(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The essence and features of administrative and legal regulation, its purpose and correlation with other concepts within administrative law of Ukraine have been clarified. It has been emphasized that legal regulation provides mainly authoritative and management function; its result is the establishment of law and order in society, it focuses on constitutional law and carries out the legalization of the principles of law. It has been determined that administrative and legal regulation is the state’s activity in order to regulate social relations with the help of the norms of law. It has been revealed that administrative and legal regulation has the relevant features that distinguish it among other types of regulation, in particular: 1) it is a mean of influence of the state on social relations; 2) it is carried out with the help of legal means, which constitute the mechanism of administrative and legal regulation; 3) its purpose is to streamline the state and authoritative relations; 4) it establishes the rights and obligations of the participants in administrative and legal relations. The authors have carried out the differentiation of the concepts of administrative and legal regulation and administrative and legal provision. It has been established that administrative and legal provision is a guarantee for the realization, security and protection of human and citizen’s rights and freedoms within administrative and legal relations and represents a set of mechanisms, tools and methods provided by the current legislation, through which administrative and legal regulation is carried out. The objective of administrative and legal regulation has been determined – it is compliance with the state policy regarding the development of administrative legal relations, creation of effective administrative, legal, economic, organizational and procedural rules; ensuring the observance and protection of human rights and freedoms, as well as their effective protection in case of violation; prevention of offenses by the subjects of administrative relations. It has been concluded that during administrative and legal regulation there are relations concerning: 1) the realization of public interests of individuals and legal entities, as well as general and public interest of the state; 2) the implementation of imperative and authoritative competence of public administration agencies; 3) the observance of certain rules established by the state within administrative and legal norms.